Donor and Recipient Matching in Facial Vascularized Composite Allotransplantation: A Closer Look at the Donor Pool. Issue 1 (July 2021) - Kauke, Martin; Haug, Valentin; Obed, Doha; Diehm, Yannick; Tchiloemba, Bianief; Safi, Ali-Farid; Pomahac, Bohdan
Abstract : Background: Identifying a donor for facial vascularized composite allotransplant recipients can be a lengthy, emotionally challenging process. Little is known about the relative distribution of key donor characteristics among potential donors. Data on actual wait times of patients are limited, making it difficult to estimate wait times for future recipients. Methods: The authors retrospectively reviewed charts of nine facial vascularized composite allotransplant patients and provide data on transplant wait times and patient characteristics. In addition, they analyzed the United Network for Organ Sharing database of dead organ donors. After excluding donors with high-risk characteristics (e.g., active cancer or risk factors for blood-borne disease transmission), the authors calculated the distribution of relevant donor-recipient matching criteria (i.e., ethnicity, body mass index, age, ABO blood group, cytomegalovirus, Epstein-Barr virus, hepatitis C virus) among 65, 201 potential donors. Results: The median wait time for a transplant was 4 months (range, 1 day to 17 months). The large majority of United Network for Organ Sharing–recorded deaths from disease were white (63 percent) and male (58 percent). Female donors of black, Hispanic, or Asian descent are underrepresented, with 7, 5, and 1 percent of all recorded deaths from disease, respectively. Potential donors show cytomegalovirus and Epstein-Barr virus seropositivity of 65 and 95 percent, respectively. The number of annual hepatitis C–positive donors increased over time. Conclusions: Actual facial vascularized composite allotransplant wait times vary considerably. Although most patients experience acceptable wait times, some with underrepresented characteristics exceed acceptable levels. Cytomegalovirus-seropositive donors present a large portion of the donor pool, and exclusion for seronegative patients may increase wait time. Hepatitis C–seropositive donors may constitute a donor pool for underrepresented patient groups in the future.